Penerapan Etika Berbusana Muslimah pada Siswi Kelas VIII SMPN 1 Danau Kembar Kabupaten Solok - Khairiyah, Muliatul; Deswalantri, Deswalantri; Jasmienti, Jasmienti; Alimir, Alimir (Indonesian Research Journal on Education, 2023)
This research was motivated by the presence of students who violated the dress code, their hair was visible when wearing the hijab, and deliberately did not give a needle to the hijab that fell down in front of the chest so that it showed their chest when their headscarf was blown by the wind. VIII at SMPN1 Danau Kembar, Solok Regency. The purpose of this study was to determine the application of Muslim dress ethics for class VIII students at SMPN1 Danau Kembar, Solok Regency. The type of research that the author uses is descriptive qualitative research. For data collection techniques the authors conduct participatory observation, in-depth interviews and documentation. The data that has been collected is then analyzed with data analysis techniques with data reduction activities, data display and conclusion drawing. To prove that this research is scientific and to test the data obtained, the author uses a data validity test with triangulation techniques. The results of the research and discussion revealed that the application of ethics in Muslim female attire at SMPN 1 Danau Kembar were: (1) functioning as a cover for genitalia, (2) not being tight, (3) not transparent, (4) not resembling men's clothes, (5 ) does not resemble the clothing of pagan women, (6) not for popularity.